Edukasi Pentingnya 1000 Hari Pertama Kehidupan dalam Manejemen Peningkatan Status Gizi Anak melalui Pendekatan Terapi Komplementer - Ni Ketut Ayu Mirayanti; Ni Komang Sukra Andini; Sang Ayu Ketut Candrawati; Ni Ketut Citrawati; Putu Gede Subhaktiyasa (Al-Qalam Institute, 2023)
The 1000 HPK period is the early period of life while still in the womb for the first 2 years of life. 1000 HPK is very important because it greatly affects the condition of growth and development of children. The focus of handling nutrition in the 1000 HPK is to prevent malnutrition which is a major health problem in toddlers because it can hinder the process of growth and development and contribute to child morbidity and mortality. Stunting is a chronic nutritional problem due to inadequate nutritional intake within the 1000 HPK period resulting in impaired growth in children. service activities carried out through the collaboration of health education institutions and health institutions, one of which aims to increase mother's knowledge about 1000 HPK, fulfill the nutritional needs of mothers and toddlers, and balanced nutrition and change in good nutritional behavior. In addition, education for cadres must also be carried out so that cadres can provide ongoing education to mothers who have toddlers.